Is Single-stage Primary Transanal Endorectal Pull through (TEP) feasible for Short Segment Hirschsprung's Disease in Neonates?- Our Experience in a Tertiary Hospital - Md Shahjahan, -; Ferdous, Kazi Md Noor ul; lslam, M Kabirul (Journal of Surgical Sciences, 2019)
Background: The surgical management of Hirschsprung's Disease (HD) includes so many procedures. TransanalEndorectal Pull through (TEP) represents the latest development in the concept of the minimally invasive surgery for HD. The purpose of this study was to evaluate the out come of the procedure in neonates. Methods: This retrospective study was carried out in a tertiary pediatric hospital during the period from January 2007 to December 2012 (5 years). The study included neonates of both sex, weight more than 2 kg, who were clinically suspected HD, radiologically transition zone at rectosigmoid and midsigmoid region and rectal biopsy proven HD and no evidence of sepsis or entrocolitis. Short segment HD with associated anomalies, and operated cases with less than 6 months' or irregular follow up were excluded. Results: During study period, single-stage transanalendorectal pull through (TEP) operation was done for short segment HD in 63 neonates, 9 patients were excluded from the study for irregular follow up. The mean operative time, mean blood loss, postoperative hospital stay, follow up period were 113 minutes, 20ml, 6.8 days and 19.6 months respectively. Transverse colostomy was needed in 6 patients for anastomotic leakage, thereafter developed anastomotic stricture, managed with regular anastomotic dilatation. Conclusion: Advancement in pediatric anesthesia, improvement of pediatric surgical expertise, perioperative management and nursing care has made single-stage primary transanalendorectal pull-through a feasible and safe surgical procedure for the treatment of short segment Hirschsprung's disease in neonate. Journal of Surgical Sciences (2014) Vol. 18 (2) : 45-50